2015
DOI: 10.1128/mcb.00945-14
|View full text |Cite
|
Sign up to set email alerts
|

PRMT4-Mediated Arginine Methylation Negatively Regulates Retinoblastoma Tumor Suppressor Protein and Promotes E2F-1 Dissociation

Abstract: The retinoblastoma protein (pRb/p105) tumor suppressor plays a pivotal role in cell cycle regulation by blockage of the G 1 -to-Sphase transition. pRb tumor suppressor activity is governed by a variety of posttranslational modifications, most notably phosphorylation by cyclin-dependent kinase (Cdk) complexes. Here we report a novel regulation of pRb through protein arginine methyltransferase 4 (PRMT4)-mediated arginine methylation, which parallels phosphorylation. PRMT4 specifically methylates pRb at the pRb C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 68 publications
2
23
0
Order By: Relevance
“…In the first, DRBD18(R→K), we mutated the three identified methylarginines to lysines, thereby creating a hypomethylated DRBD18 while preserving the residues’ positive charge. In the second methylmutant, DRBD18(R→F), we replaced the methylarginines with phenylalanine, which studies have shown can act as a methylarginine mimic ( 53 – 55 ). Because the methylarginines in DRBD18 are located in a long unstructured region of the protein (Figure 1 ), it is unlikely that mutations in this region will dramatically alter DRBD18 structure.…”
Section: Resultsmentioning
confidence: 99%
“…In the first, DRBD18(R→K), we mutated the three identified methylarginines to lysines, thereby creating a hypomethylated DRBD18 while preserving the residues’ positive charge. In the second methylmutant, DRBD18(R→F), we replaced the methylarginines with phenylalanine, which studies have shown can act as a methylarginine mimic ( 53 – 55 ). Because the methylarginines in DRBD18 are located in a long unstructured region of the protein (Figure 1 ), it is unlikely that mutations in this region will dramatically alter DRBD18 structure.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, several methyl-transferases methylate RB at K810 (Carr et al, 2011;Cho et al, 2012), K873 (Munro et al, 2010), and K860 (Saddic et al, 2010) regulating interactions that control RB's transcriptional activity and function in G1/S-checkpoint and DNA-damage response. Recently, arginine RB methylation at R775, R787, and R798 reported to reduce RB ability to retain E2F1 activity (Kim et al, 2015). Adding to this picture are potential roles for RB ubiquitination (Miwa et al, 2006) and SUMOylation (Ledl et al, 2005;Meng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The idea that pRB's binding activity is tailored by phosphorylation is only part of the story. Evidence that pRB is both acetylated and methylated in specific contexts (Chan et al 2001;Nguyen et al 2004;Leduc et al 2006;Munro et al 2010;Saddic et al 2010), evidence of interplay between different post-translational modifications (Carr et al 2011;Macdonald and Dick 2012;Munro et al 2012;Kim et al 2015), and evidence that pRB interacts with specific partners in response to cellular cues (MacLellan et al 2000;Miyake et al 2000;Dick and Dyson 2003;Nguyen et al 2004;Carr et al 2014) all suggest additional levels of diversity. Collectively, these observations raise several intriguing possibilities: (1) There may be multiple pools of pRB that perform different functions.…”
Section: How Large Is the Prb Interactome And How Is It Organized?mentioning
confidence: 99%